Influência do estado nutricional materno em vitamina A sobre os níveis de imunoglobulina A no colostro humano - Medeiros, Ana Caroline Perez (2010)
Mothers with good vitamin A nutritional status during gestation and lactation are better able to nourish and protect their infant with maternal milk. Our hypothesis is that women with more serum retinol have more retinol and secretory immunoglobulin A in colostrum. 190 healthy puerperal women from a Brazilian public maternity were recruited and divided according to the cutoff point for serum retinol (30 μg/dL). A number of the women was supplemented with 200000 UI (60 mg) of retinyl palmitate in the immediate postpartum. Serum and colostrum were collected on the 1st day postpartum and colostrum again on the following day. Retinol (serum and colostrum) was analyzed by HPLC and SIgA (colostrum) by turbidimetry. The mothers presented with adequate biochemical indicators of nutritional status, according to serum retinol (44.6 μg/dL). There were significant differences (p= 0.0017 and p= 0.043, respectively) in retinol and SIgA levels in the colostrum of mothers with serum retinol > 30 μg/dL and < 30 μg/dL. The concentration of SIgA in the colostrum of non-supplemented mothers on the 1st day postpartum was 822.6 mg/dL, decreasing after 24 hours to 343.7 mg/dL. Supplemented mothers showed levels of SIgA in colostrum of 498.9 mg/dL on the 2nd day postpartum (p= 0.00006). The colostrum of women with good vitamin A nutritional status had more retinol and SIgA. Additionally, maternal supplementation increases the levels of SIgA in colostrum. The higher levels of SIgA on the 1st day postpartum showed the importance of early breastfeeding, given that it provides considerable immunological benefits to newborn infants